The Effect of Online Shop Owner Satisfaction on Logistic Services (Comparative Study of JNE and J&T Express) - Kinda Rizki; Eko Ruddy Cahyadi; Alim Setiawan Slamet (School of Business, IPB University (SB-IPB), 2020)
Business transactions are important with the increasing of online shop in Indonesia. Every year online shops in Indonesia are increasing in accordance with the existing of technology. The impact of logistic companies as online shop partner is always improving their services to facilitate business transactions. This study aims to compare logistic services between JNE and J&T Express companies based on online shop satisfaction. The satisfaction of some online shops as both customers and working partners with the logistics companies will be important for both companies. The methods used are Importance Performance Analysis (IPA) and T-test with a sample of 150 owners. Purposive sampling is used as the sampling technique and data is collected by distributing questionnaires through online shop media social. From the fifteen attributes, important services according to online shop are responsiveness to damaged goods and lost goods, guarantees for damaged goods and lost goods, the company’s mode of communication to its customers, the company’s consistency in maintaining goods properly and consistency of delivery time to the consumer. The results of the study show that JNE and J&T Express have a significant difference, namely the superiority of JNE in maintaining goods properly inappropriate with the price their given. Meanwhile , the JNE and J & T Express have a significant inconsistency of delivery time. Keywords: importance performance analysis (ipa), customer satisfaction, logistic sevices perfomance, JNE, online shop